A Development of Online Food Ordering System for Restaurant Beiji - Wan, Jie Sin; Saringat, Mohd Zainuri (Applied Information Technology And Computer Science, 2022)
Currently, Beiji Restaurant still runs their business, processing orders through paper-based work and being handled manually by employees. It is inefficient and faces a lot of human error, resulting in the worst customer experience to order from their restaurant. Therefore, this study developed an Online Food Ordering system to help Beiji Restaurant provide better online food ordering services to customers. The project is developed as a mobile application system using a throwaway prototype method and a mobile -based language. By using this system, restaurants can receive and process orders easily. In addition, customers can also view and place orders from online easily. In addition, all users can also update the status of the order, thus customers can easily track the status of their order at any time in real time. In addition, the system emphasizes point-of-sale technology, in which administrators can view observations and report analysis of restaurant sales.